2017
DOI: 10.1590/0104-6632.20170343s20150445
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of an automatic tool for the selection of control variables based on the self-optimizing control methodology

Abstract: -Rules for control structure design for industrial processes have been extensively proposed in the literature. Some model-based methodologies have a sound mathematical basis, such as the self-optimizing control technology. The procedure can be applied with the aid of available commercial simulators, e.g., PRO/II TM and AspenPlus®, from which the converging results are obtained more suitably for industrial applications, lessening the effort needed to build an appropriate mathematical model of the plant. Motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…The criterion function for the branch-and-bound used was the minimum singular value, which fortunately has a monotonic property. For a detailed proof of it, refer to Silva et al and Cao et al…”
Section: Self Optimizing Control Technology: State-of-the-artmentioning
confidence: 99%
See 3 more Smart Citations
“…The criterion function for the branch-and-bound used was the minimum singular value, which fortunately has a monotonic property. For a detailed proof of it, refer to Silva et al and Cao et al…”
Section: Self Optimizing Control Technology: State-of-the-artmentioning
confidence: 99%
“…The gradients and Hessians with respect to the reduced space problem were obtained using the DACE toolbox and the expression derived in this work. It was necessary in this case study, to do a slight modification in the Hessian matrix J uu , to make it positively definite, performing a modified Cholesky factorization, as done in the past by Silva et al Further explanation on how this factorization is done can be found on the work of Silva et al . and Nocedal and Wright…”
Section: Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Machado (2009) avaliou a influência das variáveis operacionais, como pressão de operação e razão de refluxo, na separação das misturas de óleos lubrificantes, enquanto Orlando (2007) obteve as condições operacionais ótimas em uma coluna contendo recheio estruturado. O mesmo software foi aplicado na modelagem de um trem de destilação para determinação de condições operacionais apropriadas (SILVA, 2016), e no estudo de caso de uma torre de destilação para implementação de controle automático (SILVA et al, 2017).…”
Section: Metodologiaunclassified